Anti-inflammatory effects of ethanolic extract from Abeliophyllum distichum (Miseon Tree) leaves in mice with dextran sulfate sodium-induced ulcerative colitis - Hye-Jung Moon; Youn-Soo Cha; Kyung-Ah Kim (Food & Nutrition Research)
Abeliophyllum distichum (Miseon tree), a native Korean plant, is known for the high phenolic content in its leaves. The ethanolic leaf extracts of A. distichum have shown antioxidant, anti-obesity, and anti-inflammatory properties. However, studies on its potential to improve colitis are limited. This study aimed to determine whether the ethanolic extract of A. distichum leaves (ADE) could alleviate dextran sulfate sodium (DSS)-induced colitis in mice. The mice were divided into three groups, and the experimental group was given 300 mg/kg ADE for 4 weeks. One week before the end of the experiment, 3% DSS was added to the drinking water to induce colitis. The clinical symptoms of colitis and damage to colon tissue, including the increase in Enterobacteriaceae abundance and a decrease in Bifidobacterium in the colon, were evaluated during DSS treatment. DSS overactivated the nuclear factor (NF)-κB signaling pathway, resulting in excessive production of pro-inflammatory cytokines. In contrast, ADE alleviated the DSS-induced colitis symptoms, protected against colonic tissue damage, and restored the balance of Enterobacteriaceae and Bifidobacterium levels in the colon. Moreover, ADE effectively inhibited the DSS-induced overactivation of the NF-κB signaling pathway within the colon and mitigated abnormal inflammatory responses. These findings suggest that ADE protects against colitis by modulating the growth of some intestinal strains and the NF-κB pathway in the colon, supporting its potential as a natural agent.